PURIFIKASI DALAM PENGAJIAN, DAPAT MENGGALI KEDALAMAN ILMU DENGAN KETULUSAN HATI - Salsa Y, Nufika (Universitas Muhammadiyah Surakarta, 2022)
In Arabic the recitation is called at-ta'llimu which comes from the word ta'allama yata'alliiman which means learning. Meanwhile, the meaning of recitation itself can mean learning knowledge with a pious or knowledgeable person and has its own worship value for every Muslim. Meanwhile, linguistically the word recitation comes from the basic word